UPAYA MENINGKATKAN HASIL BELAJAR SEJARAH MELALUI METODE DISKUSI BAHASAN LKS SMP 4 LAMPUNG TAHUN 2009 - Yusinta Tia Rusdiana (Universitas Galuh, 2019)
The purpose of this class action research is to find out whether the use of the discussion method in the discussion of LKS can improve the history of learning outcomes of class VIII A of SMP 4 Padang Cermin, and also to achieve student mastery learning. The formulation of the problem in this study is